The Influence of Electronic Word of Mouth and Influencer Marketing on Purchase Intention of Facetology Skincare Products on TikTok: A Study on Generation Z in Bandar Lampung - Puspitasari, Mutiara; Roslina, Roslina; Nabila, Nuzul Inas (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to determine the effect of Electronic Word of Mouth (E-WOM) and Influencer Marketing on the purchase intention of Facetology skincare products on TikTok among Generation Z. The method used is descriptive research with data collection through questionnaires to 170 respondents, then analyzed using multiple linear regression. The results of the study indicate that the Electronic Word of Mouth (EWOM) variable on TikTok social media has a positive and significant effect on the purchase intention of Facetology products among Generation Z in Bandar Lampung, which means the better the consumer's perception of the information shared, the higher their interest in purchasing. In addition, Influencer Marketing is also proven to have a positive and significant effect indicating that the quality of promotion, credibility, attractiveness, and the ability of influencers to convey product value are important factors that motivate consumers to make purchases. The implications of this study are expected to contribute to business actors to be more competent in integrating appropriate promotional strategies using E-WOM and Influencer marketing.